Cover Feature: Survey of Zirconium‐Containing NaSICON‐type Solid‐State Li+ Ion Conductors with the Aim of Increasing Reduction Stability by Partial Cation Substitution (Batteries & Supercaps 11/2022). Issue 11 (13th October 2022) - Loutati, Asmaa; Odenwald, Philipp; Aktekin, Burak; Sann, Joachim; Guillon, Olivier; Tietz, Frank; Fattakhova‐Rohlfing, Dina
Abstract : The Cover Feature shows the kosnarite structure from an unusual perspective and with reminiscence of its volcanic origin. The analogous man‐made and so‐called NaSICON materials have been optimized with advanced processing methods. More information can be found in the Research Article by A. Loutati, F. Tietz and co‐workers .